A Three-Dimensional Simulation of Mine Ventilation Using Computational Fluid Dynamics - M Tuck; J Naser (The Australasian Institute of Mining and Metallurgy, 2005)
This paper reports a computational study using computational fluid dynamics (CFD) in a mine ventilation system. Ambient air is injected to a rectangular mine drive through a circular duct. Moisture evaporates from shaft wall depending on flow properties of air in the drive-duct system. The physical process involves simultaneous momentum, heat and mass transfer. A species transport equation is employed to account for the moisture concentration in air. The momentum equation is solved using standard k- model, while energy and species transport equations are solved using standard expressions for moisture evaporation rate and heat flux from the drive wall. The aim of this paper is to investigate effectiveness of CFD simulation in relation to mine ventilation in a drive where a significant mass transfer phenomenon occurs. Results from simulation are compared with existing data from a site in Victoria.